Characterization of agarose as immobilization matrix model for a microbial biosensor - Pernetti Mimma; Poncelet Denis; Thouand Gerald; Annesini Maria Cristina; Merli Carlo (Hemijska Industrija, 2003)
Microbial biosensors are promising tools for the detection of specific substances in different fields, such as environmental, biomedical, food or agricultural. They allow rapid measurements, no need for complex sample preparation or specialized personnel and easy handling. In order to enhance the managing, miniaturization and stability of the biosensor and to prevent cell leaching, bacteria immobilization is desirable. A systematic characterization procedure to choose a suitable immobilization method and matrix, was proposed in this study. Physical properties, storage stability mass transport phenomena and biocompatibility were evaluated, employing agarose as the model matrix. Preliminary essays with bioluminescent bacteria detecting Tributyltin were also carried out.